1996
DOI: 10.21273/jashs.121.5.794
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers Associated with Plant Architecture and Resistance to Common Blight, Web Blight, and Rust in Common Beans

Abstract: Random amplified polymorphic DNA (RAPD) markers were used to construct a partial linkage map in a recombinant inbred population derived from the common bean (Phaseolus vulgaris L.) cross BAC 6 × HT 7719 for studying the genetics of disease resistance in common bean. The linkage map spanned 545 cM and included 75 of 84 markers used in this study. The population of 128 recombinant inbred lines was evaluated for resistance to common bacterial blight, foliar resistance to web bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
64
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 25 publications
4
64
1
2
Order By: Relevance
“…However, APR was later found not to be associated with pubescence (the gene for pubescence and that for APR were located on different chromosomes), and not to be racenonspecific (Bokosi et al 1994a;Sandlin and Steadman 1994;Jung et al 1996Jung et al , 1998. This finding is in agreement with various findings for APR in cereals, summarized in van der Plank (1982).…”
Section: Single Dominantsupporting
confidence: 80%
See 4 more Smart Citations
“…However, APR was later found not to be associated with pubescence (the gene for pubescence and that for APR were located on different chromosomes), and not to be racenonspecific (Bokosi et al 1994a;Sandlin and Steadman 1994;Jung et al 1996Jung et al , 1998. This finding is in agreement with various findings for APR in cereals, summarized in van der Plank (1982).…”
Section: Single Dominantsupporting
confidence: 80%
“…Ballantyne (1978) studied the possible relationship between rust resistance and growth habit, seed coat color, and stem pigment color for various crosses but found no evidence of linkage with resistance. Jung et al (1996Jung et al ( , 1998 also found no linkage between abaxial leaf pubescence and rust resistance.…”
Section: Single Dominantmentioning
confidence: 94%
See 3 more Smart Citations